Salomé and Judith (1959) by Rosario Castellanos: building the indigenous identity and intersectionality in a dramatic poem about the Mexican Revolution - Sánchez Rodríguez, Isidora Javiera (Meridional. Revista Chilena de Estudios Latinoamericanos, 2024)
This paper analyses, from a literary and a cultural perspective, the dramatic poem Salomé y Judith (1959). This piece was written by Mexican author Rosario Castellanos and represents two war episodes, one before and the other during the Mexican Revolution. The analysis focus on exoticization and oppression mechanisms, as well as the strategic use of women and indigenous people within a group of different characters that represent social positions in Chiapas at the beginning of the 20th Century. Specifically, this work is about the representation of indigenous people in Salomé y Judith (1959) and intends to describe critically how the intersections between oppressions and gender and race identities (intersectionality) are represented. From this analysis and the dialogue with previous studies, I state that an intersectional perspective exists in the poetic and dramatic construction of Castellano’s poem.